La pedagogía en derechos humanos: una mirada desde el sur. (2019)
The consolidation of peace and democracy in Colombia requires the inclusion of women in the field of policy from the instances of decision. To fulfill this objective, it is necessary to train women in training for citizen participation. Our work consisted in carrying out the diploma in "Political Participation and Leadership of Women in the Construction of Democracy". It was made in thirteen provinces in the department of Boyacá - Colombia in which 4,000 women participated. It is important to emphasize that the diploma course is currently being developed in six municipalities. However, the paradigms and methods of the formal, scientific, theoretical education model circumscribed to the scope of the specialization of the academy, not pertinent to the specificities of the communities and the particularities of women. Based on this, we justify the analysis of this research from other theoretical references that correspond to the reality evidenced throughout the development of the work. “Epistemología del Sur” by Boaventura Sousa Santos, and “Los Siete Saberes Necesarios Para La Educación del Futuro” by Edgar Morin.